(untitled) (International Journal of Ayurveda and Pharma Research, 2018)
Ksharasutra is a medicated thread prepared by using plant based ingredients. The active ingredients are coated repeatedly on Barbour thread no 20 so that a required amount of drug gets adhered on the thread to achieve therapeutic value. Charaka mentioned Ksharasutra in the chapter of Sotha Chikitsa. Susruta mentioned its reference in Nadivrana Chikitsa. Vagvat had clearly mentioned along with Shastrakarma, Agnikarma and Ksharakarma. Chakradutta in Arshodikar clearly mentioned the idea of preparation of Ksharasutra with Snuhi Ksheera and Haridra Churna.As the name Ksharasutra itself suggest Kshara should also be one of the ingredients which was missing in the description of Chakradutta. Therefore, Kshara was added subsequently in the preparation of Ksharasutra at the department of Shalya Tantra BHU. Among the various types of Kshara, Apamarga Kshara was selected because of its better clinical efficacy, wider availability of raw material and higher yield of Kshara from the plant. Ksharasutra is a well established procedure in the management of Fistula in Ano with a high success rate. Although the standard Apamarga Ksharasutra is used successfully in the management of Fistula in Ano. Along with the advantages the standard Apamarga Ksharasutra creates many problems during preparation and application of thread. To overcome these problems various types of Ksharasutra research, preparation along with their standardization have been carried out. The research is based on searching for the drugs having better actions and acceptability than that of Snuhi Ksheera and Apamarga Kshara.